A new readiness model to enhance the assessment of organization readiness for big data implementation - Hanif Francis, Hasan Ganny; Sidi, Fatimah; Nonchi, Samsu Bahari; Ishak, Iskandar; Affendey, Lilly Suriani (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Big Data implementation plan has a number of approaches and readiness factors are to be considered to achieve higher capability of Big Data implementation and how it will benefit the organization in analyzing consumer behavior, data insight, predict the future and increase competitiveness. This paper presents a new readiness model to enhance the Assessment of Organization Readiness for Big Data implementation through qualitative method i.e. survey various organization and followed by quantitative method to validate the readiness model.